2019
DOI: 10.1021/acs.analchem.9b04302
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Mean and Distribution of Hemoglobin Content in Normal Human Blood Using Cell Tracking Velocimetry

Abstract: The current clinical method for detecting anemia focuses on measuring the concentration of hemoglobin (Hb) in blood. However, recent developments in particle tracking algorithms and the understanding of the relationship between Hb and magnetism has enabled the quantitative measurement of the Hb content in a single red blood cell, RBC, based on magnetophoretic mobility. To further explore this relationship, 22 human blood samples obtained from 17 healthy volunteers were analyzed by the cell tracking velocimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…These graphs include the settling velocity, u s , versus the magnetic velocity, u m , scatter plot with appropriate histograms aligned along the side and top, respectively. The range in distribution presented here is consistent with what we have reported earlier in a study of 17 healthy donors (Kim et al 2020). Ongoing studies are investigating the significance of these distributions in healthy, anemic and patients with sickle cell disease.…”
Section: Reactions With Rbcs and Ctvsupporting
confidence: 91%
“…These graphs include the settling velocity, u s , versus the magnetic velocity, u m , scatter plot with appropriate histograms aligned along the side and top, respectively. The range in distribution presented here is consistent with what we have reported earlier in a study of 17 healthy donors (Kim et al 2020). Ongoing studies are investigating the significance of these distributions in healthy, anemic and patients with sickle cell disease.…”
Section: Reactions With Rbcs and Ctvsupporting
confidence: 91%
“…By observing both Figure 4 and Table 1, it can be concluded that the MCH (expressed in pg of Hb per RBC) values reported by CTV are within the normal range reported for healthy individuals, between 27 and 33 pg. Moreover, our previous study assesed the performance of CTV on measuring mass of Hb on indicidual RBCs by comparing CTV results to the standard method based on spectrophotometry, and our instrument reported accurate measurements/analysis [21]. Nevertheless, when comparing the MCHC measured by CTV to the reference range of 28-41 g/dL [23], CTV measured higher MCHC due to the fact that the measured MCV is smaller than the reference range, as happened to the RDW values from the CTV instrument.…”
Section: Hemoglobin Mass and Concentration In Individual Rbcsmentioning
confidence: 86%
“…Total hemoglobin, Hb, is measured from whole blood samples by using the spectrophotometric method commonly employed in clinical laboratories, as described in our previous work [21]. Briefly, the samples obtained for spectrophotometric Hb concentration determination were diluted (4X) in deionized water in order to lyse the RBCs.…”
Section: Spectrophotometric Analysismentioning
confidence: 99%
See 2 more Smart Citations